2016
DOI: 10.1093/cercor/bhv346
|View full text |Cite
|
Sign up to set email alerts
|

Whole Transcriptome Screening Reveals Myelination Deficits in Dysplastic Human Temporal Neocortex

Abstract: Focal cortical dysplasias (FCDs) are local malformations of the human neocortex with strong epileptogenic potential. To investigate the underlying pathomechanisms, we performed a whole human transcriptome screening to compare the gene expression pattern of dysplastic versus nondysplastic temporal neocortex. Tissue obtained from FCD IIIa cases (mean age 20.5 years) who had undergone surgical treatment, due to intractable epilepsy, was compared with nondysplastic specimens (mean age 19.9 years) by means of Affym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 55 publications
6
31
1
Order By: Relevance
“…This was in line with previous studies that reported similar results (23,35,49). It was also shown previously that myelin-related mRNA transcripts are reduced in the lesional cortex of FCD patients (10).…”
Section: Discussionsupporting
confidence: 93%
“…This was in line with previous studies that reported similar results (23,35,49). It was also shown previously that myelin-related mRNA transcripts are reduced in the lesional cortex of FCD patients (10).…”
Section: Discussionsupporting
confidence: 93%
“…IHC was performed on either paraffin sections or cryosections as described before . Paraffin sections were pretreated (Tris‐buffered saline with 0.1% TritonX‐100, 1% bovine serum albumin [BSA, Sigma‐Aldrich] and incubated overnight in the rabbit monoclonal PDGFRα [platelet‐derived growth factor receptor alpha] primary antibody solution [1:500; Cell Signaling Technology] at 4°C).…”
Section: Methodsmentioning
confidence: 99%
“…Little is known about myelination disturbances in the context of FCD. Recently, we described for the first time a myelination defect in the cortical gray matter of FCD patients . So far, myelination abnormalities have been reported only for the white matter, in particular in FCD IIb cases .…”
Section: Introductionmentioning
confidence: 96%
“…For instance, triple ( plp −/− , mbp −/− , mag −/− ) mutant mice exhibit hypomyelination and high frequency seizure onset by 3 months of age . In humans, comparative whole transcriptome screening of focal cortical dysplasias (neocortical malformations with strong epileptogenic potential) into nondysplastic temporal neocortex from epilepsy patients reportedly reduced expression of myelin‐associated transcripts including mbp , mog , and mag . Moreover, experimental studies on myelin‐deficient rats have demonstrated that lack of myelin results in regional axolemmal abnormalities such as axolemmal voltage‐gated sodium channels being more diffusely distributed at higher densities.…”
Section: Discussionmentioning
confidence: 99%
“…35 In humans, comparative whole transcriptome screening of focal cortical dysplasias (neocortical malformations with strong epileptogenic potential) into nondysplastic temporal neocortex from epilepsy patients reportedly reduced expression of myelinassociated transcripts including mbp, mog, and mag. 36 Moreover, experimental studies on myelin-deficient rats have demonstrated that lack of myelin results in regional axolemmal abnormalities such as axolemmal voltage-gated sodium channels being more diffusely distributed at higher densities. It is suggested that this ion flux increase across axolemma might lead to corresponding increased extracellular potassium levels, spontaneous activity due to random opening of the channels, low threshold for excitation, and ephaptic activation of neighboring axons.…”
Section: Discussionmentioning
confidence: 99%